Pengaruh Job Demand terhadap Workplace Wellbeing pada Guru SMP Penyelenggara Pendidikan Inklusif di Kota Padang - Alifah Desita Jannah; Fidia Oktarisa (ARZUSIN, 2026)
Although teachers in inclusive schools face different work dynamics compared with teachers in regular schools, the effect of job demand on workplace wellbeing in the context of inclusive schools still requires more specific empirical investigation. This study aimed to determine the effect of job demand on workplace wellbeing among teachers at junior high schools implementing inclusive education in Padang City. This study employed a quantitative approach using the total sampling technique. The study population comprised teachers at four junior high schools implementing inclusive education with the highest number of students with special needs in Padang City, namely SMPN 7, SMPN 23, SMPN 24, and SMPN 25 Padang City, with a total sample of 192 teachers. Data were collected using the Job Demand Scale (Zulia & Susanti, 2025) and the Workplace Wellbeing Scale (Maulidina & Kadiyono, 2021), and were then analyzed using the nonparametric Spearman rho correlation test because the assumption of normality was not met. The results showed that job demand did not have a significant effect on workplace wellbeing among inclusive junior high school teachers in Padang City (sig. = 0.284 > 0.05). The categorization of each aspect also showed that both variables were at a moderate level. These findings confirm that a moderate level of job demand is not sufficient to affect teachers’ workplace wellbeing in inclusive schools. This study contributes to strengthening the study of teacher workplace wellbeing in the context of inclusive education and serves as a basis for further research to consider other factors that play a greater role in shaping teachers’ workplace wellbeing.